It's not only about the teacher! A qualitative study into the role of school climate in primary schools' implementation of self-regulated learning. Issue 3 (2nd July 2020) - De Smul, Mona; Heirweg, Sofie; Devos, Geert; Van Keer, Hilde
ABSTRACT: Teachers play a key role in the implementation of self-regulated learning (SRL). Nevertheless, research has found that SRL implementation in primary schools remains limited. This qualitative study investigates the role of school climate, the SRL implementation history, and the role of the principal school leader in the school-wide development of SRL implementation as an educational innovation. A comparative analysis between 2 successful and 2 less successful schools as to the implementation of SRL was carried out. Interviews were administered with 15 school members. The results reveal that successful SRL schools distinguish themselves by a shared vision, sufficient and focused opportunities for professional development, and regular collaboration and communication among colleagues resulting in a collective feeling of responsibility for SRL implementation. Moreover, this is influenced by the school's SRL development history and the supportive role of the school leader. The results underline the need for more school-wide interventions regarding SRL implementation.